Efforts of Milkfish Pond Farmers in Managing Psychological Stress and Remaining Productive in The Time of the Covid-19 Pandemic - Cahyono, Bagus Dwi; Huda, Nurul; Aristawati, Evy (Nusantara Science and Technology Proceedings, 2021)
The COVID-19 pandemic has had a far-reaching impact both directly and indirectly, including milkfish farmers. The enactment of Large-Scale Social Restrictions (PSBB) and continued with the Enforcement of Restrictions on Community Activities (PPKM) will impact them. The impact can be in the form of psychological stress that can cause a decrease in mood or work passion which has implications for a decrease in their productivity. This study aims to explore how milkfish pond farmers are trying to manage their psychological stress and remain productive during the COVID-19 pandemic. This research method is qualitative by thoroughly investigating and understanding the existing phenomena, starting from data processing, data triangulation, and data analysis. The sample of this research is milkfish pond farmers and policymakers related to milkfish cultivation. The sampling technique used is snowball sampling starting from policymakers to milkfish pond farmers until saturation or similarity of answers is found from the research subjects. The results of this study indicate that milkfish pond farmers experience psychological stress and decreased mood on levels that vary from mild to moderate. However, they are still trying to stay productive during the COVID-19 pandemic. This research implies that the stress level and mood of milkfish farmers and their coping mechanisms to decrease stress levels. The contribution of this research is as basic data for further researchers to develop applied research such as safe interventions to reduce stress levels and improve the mood of milkfish pond farmers.